Struktur Komunitas Makrozoobentos di Daerah Padang Lamun Muara Sungai Riau Kota Tanjungpinang Provinsi Kepulauan Riau - Ilham Ilahi; Aras Mulyadi; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in June 2013 at Riau River Estuary inTanjungpinang City Riau Islands Province. This research aimed to find out themacrozoobenthos community structure and its relationship to seagrass vegetation.The method on the research was survey method. The existence of macrozoobenthosin this area showed the dynamic symbiosis among seagrass and marine organisms.The results also showed seagrass ecosystem had the high potential to be managed andused by communities and also increasing the fisheries productivity on coastal area.Species composition of macrozoobenthos in the area consisted of 8 species, i.e.Strombus sp, Cerithidea quadrata, Pina bicolor, Anadara sp, Anadara inflata,Atactodea striata, Asteroidea sp and Diadema sitosum. Two species of seagrassvegetation were found in this area, those were Enhalus acoroides, and Halophilaovalis. T-test analysis showed that the average of macrozoobenthos abundance oneach station differed unsignificantly (p>0,05). The regression analysis showed thatrelationship among seagrass vegetation diversity and macrozoobenthos abundancewas at r=0,35.Keywords: Riau River, Macrozoobenthos, Seagrass, Symbiont